Improving Methods for Assessing the Competitiveness of Trade Enterprises - Nizomiddinov Jahonmirzo Zukhriddinoglu; Burkhanov Aktam Usmanovich (International Journal on Integrated Education, 2022)
The relevance of the topic is that all enterprises and organizations, to a greater or lesser extent, face such a problem as competition. In order to survive in such conditions, as well as for development, it is necessary to analyze the situation in the market, as well as decide on measures to improve competitiveness.